Implementation of Islamic Law in Indonesia in Constitutionalism Politics - Fauziah Hayati (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to determine the implementation of Islamic law in Indonesia in the politics of constitutionalism. This study uses a descriptive qualitative method with a literature study approach. The result of this research is the implementation of Islamic law in constitutionalism politics is reflected in the form of laws and regulations that reflect Islam as a selector for the existence of laws and regulations that develop in Indonesia. The power of Islam will always provide control over the substance or material of existing laws and regulations, as long as they do not conflict with Islamic values and norms, then these laws and regulations will be recommended by Islamic forces. Islam will straighten according to the values of goodness and truth of Islam.